Electrical Properties of Some Polymeric Complexes - Aswar, A.S.; Bhave, N.S. (Asian Journal of Chemistry, 2010)
The D.C. conductivities of Mn(II), Fe(II), Co(II), Ni(II) and Cu(II) polychelates of 4,4´-dihydroxy-3,3´-diacetyl biphenyl dithiooxamide (DDBDO), 4,4´-dihydroxy 3,3´-diacetyl biphenyl diaminopyridine (DDBDP) and 4,4´-dihydroxy-3,3´-diacetyl biphenyl diaminonapthalene (DDBDN) have been studied in their pellet form. All the polychelates show semiconducting behaviour in the range 293 to 520ºK. The value of activation energy lies in the range 0.163 to 0.642 eV.